Synthesis of Potent CERT Inhibitor HPA-12 Featuring a Tandem Corey–Link and Intramolecular Nucleophilic Acyl Substitution Reaction - Snider, Jason R.; Entrekin, Jordan T.; Snowden, Timothy S.; Dolliver, Debra (Synthesis, 2013)
A novel preparation of the potent CERT protein inhibitor (1R,3S)-HPA-12 is described. The synthesis is accomplished in five steps from (S)-Wynberg lactone and features a diastereoselective tandem Corey–Link and intramolecular nucleophilic acyl substitution reaction in a key step.
Keywords: HPA-12; CERT protein; gem-dichloroepoxide; Corey–Link reaction; Wynberg lactone